Niche dynamics of sympatric non‐breeding shearwaters under varying prey availability. (11th October 2019) - Carvalho, Paloma C.; Davoren, Gail K.
Abstract : Variation in prey availability can cause changes in species interactions among marine predators. Foraging theory predicts that niche breadth will expand when resources become limited, possibly leading to higher niche overlap among sympatric species; however, a species' niche can become constrained by interactions with other similar species, resulting in an inability to shift niche breadth or position. In coastal Newfoundland, Capelin Mallotus villosus is the main forage fish species and its availability (i.e. biomass) during the summer has varied considerably following a population collapse in the 1990s. During the summer, non‐breeding Great and Sooty Shearwaters Ardenna gravis and A. grisea migrate and aggregate at annually persistent Capelin spawning sites. We used stable isotope ratios ( δ 13 C, δ 15 N) of blood components (plasma, red blood cells) to investigate variation in isotopic niche breadth (95% prediction ellipse areas) and overlap of the two shearwater species during 2014, 2015 and 2016. Capelin availability varied among years, illustrated by lower peak biomass in 2015 (0.126 g/m²) and 2016 (0.027 g/m²) relative to 2014 (0.254 g/m²). The isotopic niche breadth (plasma) of both shearwater species expanded similarly from 2014 (0.65–0.66‰²) to 2015 (2.22–2.57‰²) and 2016 (1.15–1.42‰²), suggesting the incorporation of alternative prey types into their diet during years of lower prey availability. Isotopic niche overlap between Great and Sooty Shearwaters remained high across years (44–63%), however, providing little evidence for dietary niche partitioning during years of lower prey availability. Findings suggest that both shearwater species are flexible foragers and can modify their diet during the non‐breeding season to accommodate fluctuations in prey availability.